PENGARUH PELATIHAN KERJA, JAMINAN SOSIAL DAN PEMBERIAN INSENTIF TERHADAP KINERJA KARYAWAN GRAGE HOTEL BENGKULU - Slamat Anjoni; Ratnawili Ratnawili (Yayasan Insani Mandiri Santani, 2023)
This study aims to determine the effect of job training, social security and incentives on employee performance at Grage Hotel Bengkulu. This research is a quantitative research with a sample of 58 respondents. The sampling technique in this study is total sampling. Data collection techniques using observation, interviews and questionnaires. Data analysis techniques using instrument testing, classical assumption test, multiple linear regression analysis, coefficient of determination and hypothesis testing. The results of this test can be seen from the multiple linear regression analysis using SPSS, namely, Y = 9.118 + 0.162X1 + 0.215X2 + 0.305X3. From the results of hypothesis testing, namely, Job Training variable (X1) has a significant effect on employee performance at Grage Hotel Bengkulu with t count > t table (2,362 > 2,004). Social Security variable (X2) has a significant effect on employee performance at Grage Hotel Bengkulu with t count > t table (2.283 > 2.004). Incentive variable (X3) has a significant effect on employee performance at Grage Hotel Bengkulu with t count > t table (3.567 > 2.004). Job Training, Social Security and Incentives together have an effect on the performance of Grage Hotel Bengkulu employees with a calculated F value > F table (20.211 2.77) Keywords: Job Training, Social Security, Incentives and Employee Performance